Preclinical Test of Dacomitinib, an Irreversible EGFR Inhibitor, Confirms Its Effectiveness for Glioblastoma - Zahonero, Cristina; Aguilera, Pilar; Ramírez-Castillejo, Carmen; Pajares, Marta; Bolós, Maria Victoria; Cantero, Diana; Perez-Nuñez, Angel; Hernández-Laín, Aurelio; Sánchez-Gómez, Pilar; Sepúlveda, Juan Manuel (Molecular cancer therapeutics, 2015)
Glioblastomas (GBM) are devastating tumors in which there has been little clinical improvement in the last decades. New molecularly directed therapies are under development. EGFR is one of the most promising targets, as this receptor is mutated and/or overexpressed in nearly half of the GBMs. However, the results obtained with first-generation tyrosine-kinase inhibitors have been disappointing with no clear predictive markers of tumor response. Here, we have tested the antitumoral efficacy of a second-generation inhibitor, dacomitinib (PF299804, Pfizer), that binds in an irreversible way to the receptor. Our results confirm that dacomitinib has an effect on cell viability, self-renewal, and proliferation in EGFR-amplified ± EGFRvIII GBM cells. Moreover, systemic administration of dacomitinib strongly impaired the in vivo tumor growth rate of these EGFR-amplified cell lines, with a decrease in the expression of stem cell–related markers. However, continuous administration of the compound was required to maintain the antitumor effect. The data presented here confirm that dacomitinib clearly affects receptor signaling in vivo and that its strong antitumoral effect is independent of the presence of mutant receptor isoforms although it could be affected by the PTEN status (as it is less effective in a PTEN-deleted GBM line). Dacomitinib is being tested in second line for EGFR-amplified GBMs. We hope that our results could help to select retrospectively molecular determinants of this response and to implement future trials with dacomitinib (alone or in combination with other inhibitors) in newly diagnosed GBMs. Mol Cancer Ther; 14(7); 1548–58. ©2015 AACR.